HPV vaccine-related thyroid adverse events: temporal patterns and reporting trends - Song, Liying; Di, Jingkai; Fan, Jiaolin; Xi, Rongrong; Liang, Siyu; Duan, Guosheng; Ding, Yuanzheng; Hao, Shuai; Liu, Jing (Frontiers in Pharmacology, 2025)
BackgroundHuman papillomavirus (HPV) vaccination is essential for cervical cancer prevention, but concerns about thyroid-related adverse events (AEs) have emerged.MethodsThis pharmacovigilance study aimed to assess potential associations between HPV vaccination and thyroid disorders using spontaneous report data. Reports from the U.S. Vaccine Adverse Event Reporting System through 31 December 2024, were analyzed. Disproportionality analyses (PRR, ROR, BCPNN, MGPS) were performed, with subgroup analyses by gender, age, and vaccine type. A Weibull shape parameter model assessed the temporal risk pattern.ResultsAmong 60,840 HPV vaccine-related reports, 13 thyroid-associated AEs showed positive signals. Hypothyroidism (ROR = 11.65) and autoimmune thyroiditis (ROR = 4.26) were the strongest signals. Most cases occurred in females under 65 years. HPV-4 was linked to 72.8% of thyroid AEs. The cumulative reporting rate reached 69.1% within 180 days.ConclusionOur findings suggest a potential association between HPV vaccination and thyroid disorders, notably hypothyroidism and autoimmune thyroiditis. Continued pharmacovigilance and further mechanistic investigations are needed.